The Sustainability of Community Library and Literacy Culture - Wahyu Handayani Setyaningsih; Mery Kharismawati (Soshum: Jurnal Sosial dan Humaniora, 2021)
Community library is an institution that aims to improve the culture of literacy. It is held by several member of the society. However, community library faces several problems that hinder development, including regeneration problems in the organizational management. The library is generally located in the house of a resident, so its accessibility is very dependent on the existence of the homeowner. The homeowner is also the manager of the library. Therefore, regeneration in management is very important. The lack of awareness of community members causes the problem in the regeneration. This paper discusses the problem on sustainability of the community library. The data was taken from one of the community library in Bantul Regency, namely Widuri Pandan. The results of observations and interviews indicate that: 1) collaboration is needed with various parties to be able to develop the community, not only through donations, but also collaboration activities; 2) it is necessary to design forms of routine activities that can stimulate public interest in literacy; 3) sustainability in the human resources development faces some obstacles, so that regeneration and formation of the literacy team need to be formed.